Differential ferroptosis regulation in red and white gastrocnemius under obesity and its Attenuation by exercise and dietary restriction - Fujue Ji; Haesung Lee; Hyeonseung Rheem; Jiao Liu; Jong-Hee Kim (Scientific Reports)
Abstract Obesity is a global health challenge associated with metabolic dysfunction and chronic diseases. Ferroptosis, an iron-dependent form of regulated cell death characterised by lipid peroxidation and iron accumulation, has been implicated in obesity-related muscle pathology. However, the muscle type-specific regulation of ferroptosis in obesity remains unclear. This study investigates the impact of obesity on ferroptosis-associated markers and processes in red (RG) and white (WG) gastrocnemius and evaluates the therapeutic efficacy of dietary restriction (HFR) and HFR combined with exercise (HFRV). Male C57BL/6 N mice were randomly assigned to four groups: normal diet (NDC), high-fat diet (HF), HFR, and HFRV. Body composition and motor function were assessed using dual-energy X-ray absorptiometry and performance tests. Ferroptosis markers, iron accumulation, and lipid peroxidation in RG and WG were analysed through histological, immunohistochemical, and western immunoblot techniques. Obesity impaired muscle function and reducing walking speed, strength, and endurance. In the WG, both GPX4 expression and AMPK activity were reduced, whereas in the RG, NCOA4 expression was elevated and AMPK activity was also diminished. HFRV partially reversed ferroptosis in RG by upregulating GPX4, while the effects in WG were limited. Lipid peroxidation and iron accumulation were more effectively attenuated in RG than in WG following HFRV intervention. Obesity may drive ferroptosis in RG and WG, with distinct and overlapping regulatory signals. HFRV selectively mitigates ferroptosis in RG, underscoring the need for targeted interventions to prevent obesity-related muscle dysfunction. These findings enhance the understanding of ferroptosis in metabolic health and muscle adaptation.